POLA KEMITRAAN ANTARA PT. EXPLORE LOMBOK TOUR & TRAVEL DENGAN HOTEL LOMBOK MAYURA - Patrisia Kristi Santoso; Komang Mahawira; Achlan Fahlevi Royanow (Bajang Institute, 2024)
Indonesia presents significant opportunities across various sectors, particularly in tourism, spanning from the western to the eastern regions. The travel agent business in West Nusa Tenggara, including Lombok Island, has seen rapid development. Discussing tourism invariably involves accommodation, necessitating the availability of places to stay. Hotels are categorized into two groups: starred and non-starred hotels. This study aims to understand the role of PT. Explore Lombok Tour & Travel and Lombok Mayura Hotel in providing services to tourists, as well as to explore the nature of the collaboration between PT. Explore Lombok Tour & Travel and Lombok Mayura Hotel in delivering services to hotel guests. Three key indicators will be examined in this research: service quality, forms of collaboration, and challenges in the collaboration. These indicators will provide insights into the nature and patterns of collaboration between PT. Explore Lombok Tour & Travel and Lombok Mayura Hotel in offering services to hotel guests